2004
DOI: 10.1007/s00468-003-0304-9
|View full text |Cite
|
Sign up to set email alerts
|

Picea seedlings show apparent acclimation to drought with increasing altitude in the eastern Himalaya

Abstract: We measured plant structural and physiological responses of two sympatric Picea species, Picea likiangensis (Franchet) E. Pritzel var. balfouriana and Picea asperata Masters var. retroflexa to altitude close to the treeline in the eastern Himalaya. Most measured tree characteristics differed between different altitudes, between different ages, and between shaded and un-shaded treatments. Both P. likiangensis and P. asperata had lower foliage area/stem cross-sectional area ratios, smaller specific leaf areas, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 38 publications
3
35
0
Order By: Relevance
“…Leaf samples for the carbon isotope (␦ 13 C) analysis were oven-dried for 24 h at 80 • C and homogenized by grinding in a ball mill. Stable carbon isotope abundance in combusted samples was measured with a mass spectrometer (Finnegan MAT Delta-E, Bremen, Germany), as described by Li et al (2004). The overall precision of the ı values was better than 0.1‰, as determined from repeated samples.…”
Section: Carbon Isotope Compositionmentioning
confidence: 99%
“…Leaf samples for the carbon isotope (␦ 13 C) analysis were oven-dried for 24 h at 80 • C and homogenized by grinding in a ball mill. Stable carbon isotope abundance in combusted samples was measured with a mass spectrometer (Finnegan MAT Delta-E, Bremen, Germany), as described by Li et al (2004). The overall precision of the ı values was better than 0.1‰, as determined from repeated samples.…”
Section: Carbon Isotope Compositionmentioning
confidence: 99%
“…Samples of 100 mg DW of plant material, oven-dried at 70 • C for 24 h, were homogenized by grinding in a ball mill. The stable carbon isotope abundance in the combusted samples was measured with a mass spectrometer (Finnegan MAT Delta-E) as described by Li et al (2004). The overall precision of the ı-values was better than 0.1‰, as determined from repeated samples.…”
Section: Carbon Isotope Compositionmentioning
confidence: 99%
“…Changes in the photosynthesis parameters of plants grown under N addition have been reported in Picea seedlings in many previous studies (e.g., Li et al 2004). Some studies have showed that the values of photosynthesis parameters significantly increase in Cryptomeria japonica and hybrid poplar seedlings according to the degree of N deposition, while they decrease when the amount of N exceeds the critical point (Nakaji et al 2001;Cooke et al 2005).…”
Section: Effects Of N Addition On Growth and Physiological Variables mentioning
confidence: 84%
“…Thus, drought stress resulted in increased water use efficiency. In addition, many previous observations have showed that d 13 C increases with elevation in conifer leaves (Hultin and Marshall 2000;Li et al 2004). Correlations between d 13 C and various abiotic factors over altitude gradients have been reported, including soil moisture, air temperature, atmospheric CO 2 concentration and evaporative demand (Van de Water et al 2002;Maunoury-Danger et al 2010).…”
Section: Discussionmentioning
confidence: 95%